THE AUTHOR’S CONCEPT AND THE LANGUAGE WORLD IN LETTERS BY I.S. TURGENEV (Proceedings of Southern Federal University. Philology, 2012)
Garusina T.G.Keywords: I.S. Turgenev, epistolary heritage, outlook of the writer, the author’s concept, language world, the philosophical concept of creativity, the author’s ideas and values.In the article the author’s concept and the language world in letters by I.S.Turgenev is studied. The epistolary text conveys verbally expressed knowledge of the outside world. In his letters Turgenev strives to portray the world as he sees it through the prism of his epistolary ‘Me’.